To do this problem you would first need to factor out a variable, which in this case I would want to do the first equation because it is isolated. Now the equations would look like this:
x = -2y - 1
4x - 4y = 20
Since we know that x is now equal to -2y - 1 we can plug it in to the x value in the second equation:
4 (-2y -1) - 4y = 20
-8y -4 - 4y
-12y - 4 = 20
-12y = 24
y = -2
Now that we know the y value plug the y value to one equation to find the x, I will be using the first equation
x + 2(-2) = -1
x - 4 = -1
x = 3
Solutions:
y = -2
x = 3
Answer:
b
Step-by-step explanation:
duxuejdbdhwuskisisiei
Answer:
CDEF
Step-by-step explanation:
if the x value doesnt repeat then it is
Unfortunately, you haven't shared "the following points."
The equation of a circle centered at the origin and whose radius is 10 is
x^2 + y^2 = 10^2.
Get into form (x-h)^2=4p(y-k)
vetex is (h,k)
so
1/2(x-7)^2=y+4
times 2 both sides
(x-7)^2=2(y+4)
(x-7)^2=4(1/2)(y-(-4))
vertex is (7,-4)